Phenotypic Modulation of Biofilm Formation in a Staphylococcus epidermidis Orthopedic Clinical Isolate Grown Under Different Mechanical Stimuli: Contribution From a Combined Proteomic Study - Bottagisio, Marta; Barbacini, Pietro; Bidossi, Alessandro; Torretta, Enrica; deLancey-Pulcini, Elinor; Gelfi, Cecilia; James, Garth A.; Lovati, Arianna B.; Capitanio, Daniele (Frontiers in Microbiology, 2020)
One of the major causes of prosthetic joint failure is infection. Recently, coagulase negative Staphylococcus epidermidis has been identified as an emergent, nosocomial pathogen involved in subclinical prosthetic joint infections (PJIs). The diagnosis of PJIs mediated by S. epidermidis is usually complex and difficult due to the absence of acute clinical signs derived from the host immune system response. Therefore, analysis of protein patterns in biofilm-producing S. epidermidis allows for the examination of the molecular basis of biofilm formation. Thus, in the present study, the proteome of a clinical isolate S. epidermidis was analyzed when cultured in its planktonic or sessile form to examine protein expression changes depending on culture conditions. After 24 hours of culture, sessile bacteria exhibited increased gene expression for ribosomal activity and for production of proteins related to the initial attachment phase, involved in the capsular polysaccharide/adhesin, surface associated proteins and peptidoglycan biosynthesis. Likewise, planktonic S. epidermidis was able to aggregate after 24 hours, synthesizing the accumulation associate protein and cell-wall molecules through the activation of the YycFG and ArlRS, two component regulatory pathways. Prolonged culture under vigorous agitation generated a stressful growing environment triggering aggregation in a biofilm-like matrix as a mechanism to survive harsh conditions. Further studies will be essential to support these findings in order to further delineate the complex mechanisms of biofilm formation of S. epidermidis and they could provide the groundwork for the development of new drugs against biofilm-related infections, as well as the identification of novel biomarkers of subclinical or chronic infections mediated by these emerging, low virulence pathogens.